Burung Sebagai Subjek Reka Corak Ukkil Motif Senjata Tradisional Bajau Sama: Satu Pemerhatian Umum Bird As A Design Subject In The Ukkil Motif Of Bajau Sama Traditional Weaponry: A General Note - Mohammed Iqbal Badaruddin; Simon Soon; Luqman Lee; Zaimie Sahibil; Mohd Shahrul Hisham Ahmad Tarmizi (2020)
The value of wood carving motifs design created by the Bajau Sama craftsmens in Kota Belud is one of the uniqueness inherited by the Bajau ethnic groups in Sabah. This study discusses the uniqueness of Bajau wood carving motifs design with a bird as its source of inspiration. The subject of birds is appreciated in the design of Bajau traditional weapons. Birds that are used include burung Pimping, roasters (manuk) and dragons (naga). This study interpretes the value of Bajau woodcarvers in the design of bird-based motifs and their relationship to the cultural value of the Bajau Sama community in Kota Belud. This study has applied the process of collecting primary and secondary data. The primary data involved interviews with Bajau woodcarvers and observation of the carved motifs. Meanwhile, secondary data were collected from rjournals and books related to the art of wood carving in Malay world. The authors apply the principles of traditional Malay art and craft and the Semantic Differential method in analyzing the wood carving motifs. This observation is expected to provide a general understanding in the effort to fill in the literature gap of documentation and interpretation of the Bajau Sama motifs design especially on the subject of bird.